2015
DOI: 10.1111/andr.12035
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced fertility prediction of cryopreserved boar spermatozoa using novel sperm function assessment

Abstract: SUMMARYDue to reduced fertility, cryopreserved semen is seldom used for commercial porcine artificial insemination (AI). Predicting the fertility of individual frozen ejaculates for selection of higher quality semen prior to AI would increase overall success. Our objective was to test novel and traditional laboratory analyses to identify characteristics of cryopreserved spermatozoa that are related to boar fertility. Traditional post-thaw analyses of motility, viability, and acrosome integrity were performed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 49 publications
(67 reference statements)
2
11
0
Order By: Relevance
“…Evidence has shown that the evaluation of various sperm traits rather than a single trait analysis provides a better fertility prediction of FT semen [27][28][29]. Several sperm attributes have been used to assess the post-thaw quality of boar semen, and among these sperm motility is widely used in semen quality assessment because it correlates with fertility outcomes [30,31]. Sperm motility is assessed subjectively or with the computer-assisted semen analysis (CASA) system; however, subjective motility assessment has been shown to provide reliable estimates in association studies [26,32,33].…”
Section: Snp Associations With Post-thaw Semen Qualitymentioning
confidence: 99%
“…Evidence has shown that the evaluation of various sperm traits rather than a single trait analysis provides a better fertility prediction of FT semen [27][28][29]. Several sperm attributes have been used to assess the post-thaw quality of boar semen, and among these sperm motility is widely used in semen quality assessment because it correlates with fertility outcomes [30,31]. Sperm motility is assessed subjectively or with the computer-assisted semen analysis (CASA) system; however, subjective motility assessment has been shown to provide reliable estimates in association studies [26,32,33].…”
Section: Snp Associations With Post-thaw Semen Qualitymentioning
confidence: 99%
“…The obtained results are confirmed by the indicator of intervals between collections (Table 2). Searching for tools and information supporting the decision making process concerning the selection of boars for a station encompasses the possibility of using regression analysis (Daigneault et al, 2015;Knecht et al, 2017b;Quintero-Moreno et al, 2004). In the present study, the possibility of obtaining additional data based on multiple regression analysis was proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Our solution forms part of the discussion undertaken by Knecht et al (2017b), who showed that regression equations, in which boar's age, the interval between semen collections, and the time of semen collection were included as independent variables, allow the assessment of semen parameters with a high degree of precision. In other studies, (Daigneault et al, 2015), it was stated that regression equations in which quality parameters of the semen were used as independent variables, allow the prediction of insemination efficiency (r 2 =0.87), litter size (r 2 =0.57), and allow an improvement of insemination efficiency performed by means of frozen semen. We believe it contributes to rare literature data concerning the possibility of using regression in planning insemination boars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a combination of traditional and functional assays can allow for fertility prediction with greater accuracy. Previous work has identified a correlation between sperm-oviduct epithelial cell binding and fertility (Waberski et al, 2005;Daigneault et al, 2015). This correlation is likely due to the function of the oviduct isthmic epithelium in binding and retaining sperm to form a reservoir (Gualtieri and Talevi, 2003;Rodríguez-Martínez et al, 2005;Töpfer-Petersen et al, 2008).…”
Section: Introductionmentioning
confidence: 96%